Comparison of Outcome of Proseal Laryngeal Mask Airway and Supreme Laryngeal Mask Airway in Patients Undergoing Surgery Under General Anaesthesia - Shoaib.Malik, Muhammad.Saleh, Shahneela.Raza, Muhammad.Nadeem Muneer (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the proseal laryngeal mask airway’s performance to that of the supreme laryngeal mask airway in patients undergoing surgery under general anesthesia. Study design: Descriptive-Comparative Study Settings:Department of Anesthesia, Jinnah Postgraduate Medical Centre Karachi Study duration:December 2020 to June 2021 Materials & Methods: It was estimated that 154 patients of both genders were considering elective surgery while under the effect of general anesthesia. They were between the ages of 18 and 60. Patients were not allowed to participate in the trial if they had trouble breathing, were known to have lung or heart problems, were at danger of aspiration, or had a fractured neck spine. Following the acquisition of informed permission, the selected cases were then randomly separated into two groups, one labelled group P and the other designated group S. Group P patients were given a proseal laryngeal mask, which is a form of airway. A supreme laryngeal mask was used by those in Group S. During the first twenty-four hours, the researcher checked on each patient to see if they were coughing or had sore throats. Results: More than 96% of patients with Proseal and 88% of patients with Supreme-LMA were able to successfully insert the device on their first try in our study. When it came to inserting patients, the S-LMA group performed better than the others (19.17 2.69 min vs. 23.16 1.73 min). When comparing the adverse effects of Proseal-LMA and Supreme-LMA, we found that 27.27 Vs 20.78 percent reported cough, 18.18 Vs 12.99 percent blood stains, and 20.78 Vs 3.90 percent painful throat respectively. Conclusion: The results of this study show that the supreme laryngeal mask airway is superior than the proseal laryngeal mask airway in patients undergoing surgery under general anesthesia.